VD_FINDINFO Décision / 2014 / 909 vom 11. September 2014 - VD Tribunal cantonal (2014)
CLASSEMENT DE LA PROCÉDURE, RÉCUSATION, DEMANDE ADRESSÉE À L'AUTORITÉ | 310 CPP (CH), 393 al. 1 let. a CPP (CH), 59 CPP (CH)